Forecasting the Average Temperature Rise in Bangladesh: A Time Series Analysis - Paul, Sneha; Roy, Shuvendu (Journal of Engineering Science, 2020)
Global warming has caused a significant increment in surface temperature around the world, including Bangladesh. In this study, the temperature data of Bangladesh over the past 100 years has been analyzed to see the temperature increment pattern. It has been seen that the average temperature has risen by 10C over the last century. Using daily average temperature data of Bangladesh, machine learning-based time series forecasting model has been developed to predict the future temperature of Bangladesh. The model can predict the minimum, maximum, and average temperatures of any year in the future. This has been treated as a regression problem and Linear, Polynomial, and Support Vector Regression have been proposed to build the prediction model. The proposed model has a mean square error of 0.00470C which is a good margin for such a model. Using the model, the average temperature of Bangladesh is predicted over the next hundred years. Journal of Engineering Science 11(1), 2020, 83-91